Development of the Concept of Knowledge Management - V. G. Smirnova (Управление)
The article considers the scientific contribution of the department “Theory of Management” to the development of the concept of knowledge management. The department is one of the first in our country began to study a new area of management, including research, development of the first textbooks, training programs, the creation of the new training course “knowledge management”, publication of scientific articles and monographs in the new field of management.